THE EFFECT OF TAX AVOIDANCE, TAX PROCEDURE AWARENESS, TAX SOCIALIZATION AND TAX MODERNIZATION ON TAXPAYER COMPLIANCE AT THE MEDAN PRIMARY TAX SERVICE OFFICE - Galeh Sari; Alice Paulina Purba (PT. MITRA ANGKASA INFORMATIKA, 2024)
Taxpayer's obedience is influenced by several factors such as, tax evasion, tax procedure's awareness, tax socialization and tax modernization. Tax procedure's awareness is a condition where the taxpayer understands and comprehends the meaning, function and the purpose of tax payments to the country. The purpose of this research is to verify the influences of tax evasion, tax procedure's awareness, tax socialization and tax modernization towards the taxpayer's obedience in tax service office (tax office) Pratama Medan. The methodology used in this research is a quantitative approach with questionnaire method such as distributing a list of questionsnaire. Variable is measured by Likert scale. The population in this research is all taxpayers in tax service office/tax office Prata Medan whose sum is 85,180 taxpayers with 118 samples. The results of this research show that tax evasion, tax procedure's awareness and tax socialization are not working for taxpayer's obedience, but tax modernization is partially and significantly influenced towards the taxpayer's obedience. The result of simultaneous research shows that tax evasion, tax procedure's awareness, tax socialization and tax modernization are influenced positively and significantly for taxpayer's obedience. Key Words Tax Evasion, Tax Procedure's awareness, Tax Socialization, Tax Modernization and Obedience